Analisis Nilai Entitas Setelah Penerapan Financial Technology oleh PT Bank Negara Indonesia (Persero) Tbk - Revita Chairunisa; Ferry Irawan (Keberlanjutan)
This study aims to know whether there is an increase in profit due to the implementation of financial technology by PT Bank Negara Indonesia (Persero) Tbk. The research method used is data collection and qualitative research, namely literature study by examining various books, notes, literature, internet sites, research journals, studying and comparing written information sources and statutory regulations to match the title and the topic submitted. This method is used to understand the basic understanding, theoretical basis, and concepts used to carry out analysis and evaluation of the problems discussed and is used to compare the suitability of theory with practice in the field. The results of the study show that there are profits obtained by BNI after implementing fintech. Although financial technology is considered to be a threat by replacing some of its operating activities with technology, with its sophistication, fintech can provide convenience for its customers with all its effectiveness and efficiency so that the demand for existing facilities in the products offered by BNI is increasing according to customer needs. This impacts the increase in profits generated by operating activities in financial services carried out by BNI.